Chemical durability of borosilicate pharmaceutical glasses: Mixed alkaline earth effect with varying [MgO]/[CaO] ratio. Issue 8 (28th April 2021) - Yang, Rui; Liu, Hongshen; Ding, Zhijie; Zheng, Jinfeng; Mauro, John C.; Kim, Seong H.; Zheng, Qiuju
Abstract: Glass for pharmaceutical packaging requires high chemical durability for the safe storage and distribution of newly developed medicines. In borosilicate pharmaceutical glasses which typically contain a mixture of different modifier ions (alkali or alkaline earth), the dependence of the chemical durability on alkaline earth oxide concentrations is not well understood. Here, we have designed a series of borosilicate glasses with systematic substitutions of CaO with MgO while keeping their total concentrations at 13 mol% and a fixed Na2 O concentration of 12.7 mol%. We used these glasses to investigate the influence of R  = [MgO]/([MgO] + [CaO]) on the resistance to aqueous corrosion at 80°C for 40 days. It was found that this type of borosilicate glass undergoes both leaching of modifier ions through an ion exchange process and etching of the glass network, leading to dissolution of the glass surface. Based on the concentration analysis of the Si and B species dissolved into the solution phase, the dissolved layer thickness was found to increase from ~100 to ~170 nm as R increases from 0 to 1. The depth profiling analysis of the glasses retrieved from the solution showed that the concentration of modifier ions (Na +, Ca 2+, and Mg 2+ ) at the interface between the solution and the corroded glass surface decreased to around 40%–60% of the corresponding bulk concentrations, regardless of R and the leaching of modifier cations resulted in a silica‐rich layer in the surface. The leaching of Ca 2+ and Mg 2+ ions occurred within ~50 and <25 nm, respectively, from the glass surface and this thickness was not a strong function of R . The leaching of Na + ions varied monotonically; the thickness of the Na + depletion layer increased from ~100 nm at R  = 0 to ~200 nm at R  = 1. Vibrational spectroscopy analysis suggested that the partial depletion of the ions may have caused some degree of the network re‐arrangement or re‐polymerization in the corroded layer. Overall, these results suggested that for the borosilicate glass, replacing [CaO] with [MgO] deteriorates the chemical durability in aqueous solution.